Organocatalytic sequential alpha-amination/corey-chaykovsky reaction of aldehydes: a high yield synthesis of 4-hydroxypyrazolidine derivatives - Kumar, B. Senthil; Venkataramasubramanian, V.; Sudalai, Arumugam (Organic Letters, 2012)
A tandem reaction of in situ generated a-amino aldehydes with dimethyloxosulfonium methylide under Corey-Chaykovsky reaction conditions proceeds efficiently to give 4-hydroxypyrazolidine derivatives in high yields with excellent enantio- and diastereoselectivities. This organocatalytic sequential method provides for the efficient synthesis of anti-1,2-aminoalcohols, structural subunits present in several bioactive molecules as well.

Proline catalyzed sequential alpha-aminooxylation or -amination/reductive cyclization of o-nitrohydrocinnamaldehydes: a high yield synthesis of chiral 3-substituted tetrahydroquinolines - Rawat, Varun; Kumar, B. Senthil; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2013)
A new sequential organocatalytic method for the synthesis of chiral 3-substituted (X = OH, NH2) tetrahydroquinoline derivatives (THQs) [ee up to 99%, yield up to 87%] based on alpha-aminooxylation or -amination followed by reductive cyclization of o-nitrohydrocinnamaldehydes has been described. This methodology has been efficiently demonstrated in the synthesis of two important bioactive molecules namely (-)-sumanirole (96% ee) and 1-[(S)-3-(dimethylamino)-3,4-dihydro-6,7-dimethoxy-quinolin-1(2H)-yl]- propanone (92% ee).

One-pot synthesis of cyclic carbonates from aldehydes, sulfur ylide, and CO2 - Aher, Ravindra D.; Kumar, B. Senthil; Sudalai, Arumugam (Synlett, 2014)
Treatment of aldehydes with sulfur ylide (CH2=SOMe2 or CH2=SMe2), in the presence of CO2 (1 atm) bubbled sequentially under mild conditions, produces cyclic carbonates in preparative yields. Sodium iodide formed in situ promotes the reaction between epoxide as intermediate and CO2 at ambient conditions, thus constituting a powerful metal-free synthesis of organic cyclic carbonates directly from aldehydes.
Keywords: Carbon dioxide; cyclic carbonates; cyclization; epoxides; Insertion

Enantioselective synthesis of guggultetrol and D-ribo-phytosphingosine tetraacetate via L-proline catalyzed sequential alpha-aminooxylation/Horner-Wardsworth-Emmons olefination-Sharpless asymmetric dihydroxylation strategy - Venkataramasubramanian, V.; Kumar, B. Senthil; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2015)
An efficient enantioselective synthesis of two bioactive molecules, that is, guggultetrol and D-ribo-phytosphingosine, is described with high enantioselectivity (>98% ee) starting from commercially available 1-hexadecanol. The synthesis comprises organocatalyzed sequential alpha-aminooxylation of an aldehyde followed by Horner-Wardsworth-Emmons olefination and Sharp less asymmetric dihydroxylation as the key chiral inducing steps. For both syntheses, gamma-hydroxy-alpha,beta-unsaturated ester serves as the common intermediate obtained from proline catalysis. (C) 2015 Elsevier Ltd. All rights reserved.

Proline-catalyzed sequential syn-mannich and [4+1]-annulation cascade reactions to form densely functionalized pyrrolidines - Aher, Ravindra D.; Kumar, B. Senthil; Sudalai, Arumugam (Journal of Organic Chemistry, 2015)
A highly efficient one-pot [4 + 1]-annulation process for the asymmetric synthesis of densely functionalized pyrrolidine derivatives is described. The in situ generated syn-Mannich adduct obtained via proline catalysis acts as a four-atom component, and Coreys sulfur ylide or ethyl bromoacetate acts as a one-atom carbon source to construct pyrrolidine units in a highly enantio- and diastereoselective manner.

"Metal-free'' synthesis of 1,2,3-triazoles via tandem azidation, intramolecular [3+2]-cycloaddition and aromatization of ethyl acrylate derivatives - Kumar, B. Senthil; Gadakh, Sunita; Sudalai, Arumugam (Tetrahedron Letters, 2018)
An efficient ``one-pot'' method for the synthesis of substituted 1,2,3-triazole derivatives in excellent yields as single regioisomer is reported. The key transformation involves an atom-efficient tandem azidation, intramolecular [3+2]-cycloaddition and aromatization of acrylate derivatives on treatment with NaN3 in DMF under mild conditions. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Intramolecular cycloaddition; Regioselective; Tandem azidation; triazoles

Concise enantioselective synthesis of (R)-(+)-goniothalamin oxide, a trypanocidal active agent via L-prolinol catalyzed asymmetric epoxidation of cinnamaldehyde - Kumar, B. Senthil; Mandle, Ram D.; Kamble, Sanjay P.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2020)
A short and straight-forward enantioselective synthesis of (R)-(+)-goniothalamin oxide 2 has been achieved with an overall yield of 39% and 99% ee. The synthetic approach involves L-prolinol catalyzed asymmetric epoxidation of cinnamaldehyde followed by Lewis acid-mediated diastereoselective allylation of epoxy aldehyde as the key chiral-inducing steps.
Keywords: Allylation; asymmetric epoxidation; Esterification; Grubbs' catalyst; L-prolinol catalyst; Ring closing metathesis